Automated detection of myopic maculopathy using five-category models based on vision outlooker for visual recognition - Wan, Cheng; Fang, Jiyi; Hua, Xiao; Chen, Lu; Zhang, Shaochong; Yang, Weihua (Frontiers in Computational Neuroscience, 2023)
Purpose: To propose a five-category model for the automatic detection of myopic macular lesions to help grassroots medical institutions conduct preliminary screening of myopic macular lesions from limited number of color fundus images. Methods: First, 1750 fundus images of non-myopic retinal lesions and four categories of pathological myopic maculopathy were collected, graded, and labeled. Subsequently, three five-classification models based on Vision Outlooker for Visual Recognition (VOLO), EfficientNetV2, and ResNet50 for detecting myopic maculopathy were trained with data-augmented images, and the diagnostic results of the different trained models were compared and analyzed. The main evaluation metrics were sensitivity, specificity, PPV, NPV, area under the curve (AUC), kappa and accuracy, and receiver operating characteristic curve (ROC). Results: The diagnostic accuracy of the VOLO-D2 model was 96.60% with a kappa value of 95.60%. All indicators used for the diagnosis of myopia-free macular degeneration were 100%. The sensitivity, negative predictive value (NPV), specificity, and positive predictive value (PPV) for diagnosis of leopard fundus were 96.43%, 98.33%, 100%, and 100%, respectively. The sensitivity, specificity, PPV, and NPV for the diagnosis of diffuse chorioretinal atrophy were 96.88%, 98.59%, 93.94%, and 99.29%, respectively. The sensitivity, specificity, PPV, and NPV for the diagnosis of patchy chorioretinal atrophy were 92.31%, 99.26%, 97.30%, and 97.81%, respectively. The sensitivity, specificity, PPV, and NPV for the diagnosis of macular atrophy were 100%, 98.10%, 84.21%, and 100%, respectively. Conclusion: The VOLO-D2 model accurately identified myopia-free macular lesions and four pathological myopia-related macular lesions with high sensitivity and specificity. It can be used in screening pathological myopic macular lesions and can help ophthalmologists and primary medical institution providers complete the initial screening diagnosis of patients.